2019
DOI: 10.1002/jgc4.1087
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting breast cancer patients' need for genetic risk information: From information insufficiency to information need

Abstract: Information‐seeking models typically focus on information‐seeking behaviors based on individuals' interest in information, because their current level is perceived to be insufficient. In the context of genetic risk information (GRI), however, information insufficiency is difficult to measure and thus can limit understanding of information behavior in the context of GRI. We propose that an individual's need for information might be a more direct and conceptually clearer alternative to predicting their informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
(136 reference statements)
0
5
1
Order By: Relevance
“…Those who speak a language other than that being used in the study (or in clinic) likely to need aids to facilitate understanding. No other variables were associated with result preference, which is contrary to earlier studies [5,12,13] which identified a range of demographic and psychological predictors of preferences. For example, Guo et al [12] and Kaphingst et al [5] found that young women with breast cancer who had genetically related children were interested in carrier status regardless of actionability, whereas this variable was not associated with any result return preference in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Those who speak a language other than that being used in the study (or in clinic) likely to need aids to facilitate understanding. No other variables were associated with result preference, which is contrary to earlier studies [5,12,13] which identified a range of demographic and psychological predictors of preferences. For example, Guo et al [12] and Kaphingst et al [5] found that young women with breast cancer who had genetically related children were interested in carrier status regardless of actionability, whereas this variable was not associated with any result return preference in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies suggest that patients consider results with personal utility (such as for reproductive purposes) to be 'actionable', while researchers typically consider those with clinical utility to be 'actionable' [7,8] and therefore worthy of return [9][10][11]. Research also suggests that a person's preferences may be impacted by psychological factors, such as knowledge, worry about genetic risks [5], having genetically related children [12] and genetic causal beliefs [13], so that healthcare providers and patients may view the same results differently. These findings have implications for counselling prior to testing to manage patient expectations as well as for deciding which results to produce and return.…”
Section: Introductionmentioning
confidence: 99%
“…In another analysis using rating scale data from this survey, high genetic causal belief was found to be related to strong interest in learning genetic risk information for results associated with preventable and treatable diseases (Hong et al, ). In this analysis with the ranking scale, we found that participants with higher genetic causal beliefs were more likely to rank non‐actionable results as their top choice for return than either actionable or carrier status results.…”
Section: Introductionmentioning
confidence: 93%
“…The results suggested that psychological factors were related to the preferences; participants with more knowledge about sequencing benefits, higher worry about genetic risks, and stronger health information orientation were more likely to be very interested in learning each type of result while clinical factors largely were not related to these preferences (Kaphingst et al, ). Here, we examine the association between psychological and clinical predictors and preferences for return of results using the ranking of the seven types of sequencing results and compare similarities and differences to the previous analysis using the rating scale (Hong, Biesecker, Ivanovich, Goodman, & Kaphingst, ; Kaphingst et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…47 The need for genetic risk information, such as when contemplating testing for the BRCA mutation after breast cancer diagnosis, has been shown to predict information seeking behavior. 48 Lack of understanding laws and regulations that govern data sharing hamper some researchers. 49 Though most people have general awareness related to the Health Insurance Portability and Accountability Act and the Genetic Information Nondiscrimination Act, regulations related to biobank operation may be less familiar, particularly when researchers take part in international initiatives.…”
Section: The Research Viewmentioning
confidence: 99%